PENERAPAN IRIGASI MIKRO,TUMPANGSARI DAN MULSA UNTUK MENGANTISIPASI KEHILANGAN HASIL CABAI MERAH PADA PENANAMAN DI MUSIM KEMARAU(APPLICATION OF MICRO IRRIGATION MULTIPLECROPPING AND MULCH FOR PEPPER YIELD LOST ANTICIPATION ON DRY SEASON) - Meinarti Norma S; Sodiq Jauhari (Agromet, 2008)
Precipitation indicates system and intensity planting area. For anticipation plant on dry season, farmers from mountain range use water which was saving in plastic tank at teras bangku. This study has done at Canggal, Kledung, Temanggung on dry season;18 September 2006 till 19 December 2006. Climate, agronomy and soil water content were analyzed using dailiy crop water balance (CWB-ETO).The treatment which application were : a)once irrigation every three days, b) irrigation every das, c)not use mulch and d)use mulch. Yield lost on dry season (plant date at March till September) at 100 % and 20 % is plant date at January till Februari. At Sudirjo field, yield lost at 0 % on dry season plant date. Production of pepper at Sudirjo field 0..6 kg/plnt and secundar date of tomat production is 1.6 kg/platn until 1.2 kg/plantt.Difference of yield lost between Sudirjo field and from CWB-ETO simulation needs good analysis which base for CWB-ETO program.